2021
DOI: 10.3892/ol.2021.13089
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib treatment of metastatic melanoma with c‑Kit aberration reduces tumor growth and promotes survival

Abstract: Melanomas are highly malignant tumors that readily metastasize and have poor prognosis. Targeted therapy is a cornerstone of treatment for patients with melanoma. Although c-Kit gene aberration has found in 5-10% of melanoma cases, research on c-Kit inhibitors for melanoma with c-Kit aberration have been disappointing. Sorafenib is a tyrosine kinase inhibitor, whose targets include c-Kit, platelet derived growth factor receptor (PDGFR), VEGFR and RAF. The present study aimed to examine the effect of sorafenib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Since receptor and nonreceptor TK become clinically valuable target molecules for cancer therapy, our study examined not only the influence of carvedilol alone against melanoma cells but also in combination with TKI sorafenib. Studies have shown antitumor activity of sorafenib against various cancers such as breast cancer ( Zafrakas et al, 2016 ), colorectal cancer ( Kacan et al, 2016 ), and melanoma ( Takeda et al, 2021 ). The current study establishes the significant growth inhibitory effect of sorafenib on C32 amelanotic and A2058 melanotic melanoma cells after 72 h of treatment with IC50 values of 6.67 µM and 7.63 µM respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since receptor and nonreceptor TK become clinically valuable target molecules for cancer therapy, our study examined not only the influence of carvedilol alone against melanoma cells but also in combination with TKI sorafenib. Studies have shown antitumor activity of sorafenib against various cancers such as breast cancer ( Zafrakas et al, 2016 ), colorectal cancer ( Kacan et al, 2016 ), and melanoma ( Takeda et al, 2021 ). The current study establishes the significant growth inhibitory effect of sorafenib on C32 amelanotic and A2058 melanotic melanoma cells after 72 h of treatment with IC50 values of 6.67 µM and 7.63 µM respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib and imatinib elicited a better potency in the high-risk group, while gefitinib did considerably better in the low-risk group. Sorafenib was experimented to prolong OS in mice by inhibiting migration and invasion of melanoma cells and the authors speculated it to be of potential use for treating SKCM ( 44 ). As a monotherapy or in combination with chemotherapy, sorafenib is of limited use, hence it is vital to explore biomarkers to choose the suitable patients that are more likely to respond to sorafenib ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A and VEGF receptor-2 (VEGFR-2) are two chief factors in the progression of angiogenesis. Sorafenib (Sor) is a multi-kinase inhibitor that has a demonstrated history of targeting VEGFR, platelet derived growth factor receptor (PDGF), and Raf to inhibit tumor progression [ 165 ]. However, the drawbacks of Sor, such as poor solubility, rapid metabolism, and low bioavailability, hinder them from exhibiting complete action.…”
Section: Inorganic Nanoparticles For Skin Cancer Therapymentioning
confidence: 99%